1975
DOI: 10.1016/0005-2760(75)90032-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of sterol esterification in developing wheat endosperm

Abstract: Summary1. The action of gene Pin, previously characterized by the sterol ester patterns of mature whole wheat kernels, has been found to be restricted to the endosperm and not to affect the embryo, the pericarp or the seed coat.2. The dominant alíele Pin, which determines a sterol ester pattern with palmitate as the main ester, is also responsible for a low level of free sterol at maturity. A high level of free sterol is associated with the recessive alíele pin, which determines an ester pattern with linoleate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Our present and previous results [4,5] suggest that endosperm is not involved in supplying sterols to the growing tissues during germination and that, on the other hand, enough sterols are accumulated as esters in the embryo during development to serve that purpose.…”
Section: Disclssionsupporting
confidence: 50%
See 3 more Smart Citations
“…Our present and previous results [4,5] suggest that endosperm is not involved in supplying sterols to the growing tissues during germination and that, on the other hand, enough sterols are accumulated as esters in the embryo during development to serve that purpose.…”
Section: Disclssionsupporting
confidence: 50%
“…The rapid decline of scutellum sterols is concomitant with, and of the same order as, their increase in coleoptile and roots. Most of the mature embryo sterols are esterified and we have previously shown that about 2/3 of these esters are synthesized just prior to maturity, when seeds are starting to dry [5]. These facts suggest a storage role for the embryo sterol esters.…”
Section: Disclssionmentioning
confidence: 86%
See 2 more Smart Citations